YTP-1 (YRCS-1205): A promising castor variety for Tamil Nadu: YTP-1 (YRCS-1205): A promising castor variety for Tamil Nadu - S R VENKATACHALAM,; P ARUTCHENTHIL,; P KATHIRVELAN,; M DEIVAMANI, (Journal of Oilseeds Research, 2020)
Castor variety YTP-1 suitable for intercropping, mixed cropping and bund crop systems. The variety can be maintained as annual/perennial. The variety is tested across years in station trials, MLT, ART, OFT and AICRP trials. The average annual seed yield is 1484 kg/ha. As perennial the seed yield is 3 kg/plant/annum.